The glass books of the dream eaters - Dahlquist, Gordon (Bantam Books, 2006)
It begins with a simple note: Roger Bascombe wishes to inform Celeste Temple that their engagement is forthwith terminated. But Celeste, for all her lack of worldly experience, is determined to find out why her fiance? should have thrown her over so cruelly. Adopting a disguise, she follows her erstwhile lover to the forbidding Harschmort manor, where she discovers a world--by turns seductive and shocking--she could never have imagined, and a conspiracy so terrifying as to be almost beyond belief.--From publisher description.